Identification of Synergistic Drug Combinations to Target KRAS-Driven Chemoradioresistant Cancers Utilizing Tumoroid Models of Colorectal Adenocarcinoma and Recurrent Glioblastoma - Gupta, Kshama; Jones, Jeremy C.; Farias, Virginea De Araujo; Mackeyev, Yuri; Singh, Pankaj K.; Quiñones-Hinojosa, Alfredo; Krishnan, Sunil (Frontiers in Oncology, 2022)
Treatment resistance is observed in all advanced cancers. Colorectal cancer (CRC) presented as colorectal adenocarcinoma (COAD) is the second leading cause of cancer deaths worldwide. Multimodality treatment includes surgery, chemotherapy, and targeted therapies with selective utilization of immunotherapy and radiation therapy. Despite early success of anti-epidermal growth factor receptor (anti-EGFR) therapy, treatment resistance is common and often driven by mutations in APC, KRAS, RAF, PI3K/mTOR, and positive feed-back between activated-KRAS and WNT-effectors. Challenges in directly targeting WNT-regulators and KRAS have caused alternative actionable targets to gain recent attention. Utilizing an unbiased drug-screen, we identified combinatorial targeting of DDR1/BCR-ABL signaling axis with small molecule inhibitors of EGFR-ERBB2 to be potentially cytotoxic against multicellular-spheroids obtained from WNT-activated and KRAS-mutant COAD lines (HCT116, DLD1, SW480) independent of their KRAS-mutation type. Based on the data-driven approach using available patient datasets (TCGA), we constructed transcriptomic-correlations between the gene DDR1, with expression of genes for EGFR, ERBB2-4, MAPK pathway intermediates, BCR, ABL and genes for cancer stem cell reactivation, cell polarity and adhesion, and identified a positive association of DDR1 with EGFR, ERBB2, BRAF, SOX9 and VANGL2 in PanCancer. The evaluation of pathway-network using STRING database and Pathway Commons database revealed DDR1 protein to relay it’s signaling via adaptor proteins (SHC1, GRB2, SOS1) and BCR-axis to contribute to KRAS-PI3K-AKT signaling cascade, which was confirmed by western blot. We further confirmed the cytotoxic potential of our lead combination involving EGFR/ERBB2 inhibitor (Lapatinib) with DDR1/BCR-ABL inhibitor (nilotinib) in radioresistant spheroids of HCT116 (COAD), and in an additional devastating primary cancer model, glioblastoma (GBM). GBMs overexpress DDR1 and share some common genomic features with COAD like EGFR amplifications and WNT activation. Moreover, genetic alterations in genes like NF1 make GBMs to have intrinsically high KRAS activity. We show the combination Nilotinib plus Lapatinib to exhibit potent cytotoxic efficacy than either of the drugs administered alone in tumoroids of patient derived recurrent GBMs. Collectively, our findings suggest that combinatorial targeting of DDR1/BCR-ABL with EGFR-ERBB2 signaling may offer a therapeutic strategy against stem-like KRAS-driven chemo-radioresistant tumors of COAD and GBM, widening the window for its applications in main-stream cancer therapeutics.